The IBM TotalStorage NAS Gateway 500 integration guide - Tretau, Roland (IBM, 2004)
This IBM Redbooks publication describes how to install and configure the very latest IBM storage solution and concept, the IBM TotalStorage Network Attached Storage (NAS) Gateway 500, in heterogeneous environments. The IBM TotalStorage NAS Gateway 500 series is an innovative Network Attached Storage device that connects clients and servers on an IP network to Fibre Channel storage, efficiently bridging the gap between LAN storage needs and SAN storage capacities. The IBM TotalStorage NAS Gateway 500 is a storage solution for UNIX/AIX/Linux, Apple, and Microsoft Windows environments. In this book, we show how to integrate the IBM TotalStorage NAS Gateway 500 and explain how it can benefit your company's business needs. This book is an easy-to-follow guide which describes the market segment that the IBM TotalStorage NAS Gateway 500 is aimed at, and explains NAS installation, ease-of-use, remote management, expansion capabilities, high availability (two node clustering and up to four node remote mirroring), and backup and recovery techniques. It also explains open systems storage concepts and methodologies for common data sharing for UNIX/AIX/Linux, Apple, and Microsoft Windows environments. Please note that the additional material referenced in the text is not available from IBM.
"This edition applies to the IBM TotalStorage NAS Gateway 500 Release 1.1.1 as of August 2004.". - Text enhanced by pdf downloads. - Title from title screen. - Title from book cover on Web Page (viewed September 8, 2005). - Includes bibliographical references and index
Keywords: Storage area networks (Computer networks); Computer storage devices; Réseaux de stockage (Informatique); Ordinateurs; Mémoires